2019
DOI: 10.1186/s12974-019-1651-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant CC16 inhibits NLRP3/caspase-1-induced pyroptosis through p38 MAPK and ERK signaling pathways in the brain of a neonatal rat model with sepsis

Abstract: BackgroundSepsis is a critical disease associated with extremely high mortality. Some severe forms of sepsis can induce brain injury, thus causing behavioral and cognitive dysfunction. Pyroptosis is a type of cell death that differs from apoptosis and plays an important role in the occurrence and development of infectious diseases, nervous system-related diseases. A recent study has found that there is pyroptosis in the hippocampus of sepsis-induced brain injury, but its mechanism and treatment scheme have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 43 publications
(36 reference statements)
4
48
0
Order By: Relevance
“…Those studies suggested that exogenous supplementation of recombinant CC16 could ameliorate cigarette smoke-induced lung inflammation in a murine disease model of chronic obstructive pulmonary disease [ 28 ]. Zhou et al suggested that CC16 is an inhibitor of cell pyroptosis and inflammatory factors induced by LPS [ 29 ], demonstrating the potential value of CC16 in therapeutic efforts to repair acute lung injury induced by coronavirus disease 19 (COVID-19). Further investigations of the function of CC16 in critical care patients are needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies suggested that exogenous supplementation of recombinant CC16 could ameliorate cigarette smoke-induced lung inflammation in a murine disease model of chronic obstructive pulmonary disease [ 28 ]. Zhou et al suggested that CC16 is an inhibitor of cell pyroptosis and inflammatory factors induced by LPS [ 29 ], demonstrating the potential value of CC16 in therapeutic efforts to repair acute lung injury induced by coronavirus disease 19 (COVID-19). Further investigations of the function of CC16 in critical care patients are needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, we have demonstrated that pyroptosis plays a role in the degeneration of striatal neurons in HD, and we infer that counteracting the process and the inflammasome with appropriate compounds could be beneficial in fighting Huntington’s disease 37 .…”
Section: Discussionmentioning
confidence: 93%
“…Because p38 MAPK plays a role in the process of apoptosis, the p38 MAPK inhibitor SB203580 has been used to decrease p38 MAPK activation by many researchers [25,26]. In this study, to verify that the inhibition of p38 MAPK activity has an antiapoptotic effect, U46619, an agonist of p38 MAPK, was applied [27,28]. Our results demonstrated that the 25 mg mL −1 QKF + SB203580 group, but not the U46619-treated group, exhibited increased preservation of neuronal morphology, enhanced neuron viability, a decreased number of TUNEL-positive cells, upregulated expression of an antiapoptotic protein, and downregulated expression of proapoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Horseradish peroxidase-(HRP-) conjugated IgG secondary antibody was purchased from Beijing Bioss Biotechnology Co., Ltd. (Beijing, China), and the BCA protein assay kit was obtained from Beyotime Biotechnological Technology Co., Ltd. (Shanghai, China). [25][26][27][28][29][30][31][32][33][34][35] . QKF is composed of 10 herbs: Radix Rehmanniae (Sheng Di Huang), Radix Paeoniae Alba (Bai Shao), Radix Ophiopogonis (Mai dong), Cortex Moutan Radicis (Mu dan pi), Poria cocos (Fu Ling), Herba Dendrobii Rhizoma (Shi Hu), Rhizoma Acori Tatarinowii (Shi Chang Pu), Rhizoma Anemarrhenae (Zhi mu), Sophorae Flavescentis (Ku Shen), and Pericarpium Citri Reticulatae (Chenpi), all of which are recorded in the Chinese Pharmacopoeia, as being present in QKF at a ratio of 2 : 2: 2 : 2: 2 : 2: 2 : 1.5 : 1.5 : 1 on a dry-weight basis, respectively.…”
Section: Main Reagentsmentioning
confidence: 99%